Study on the Relationship between Intestinal Microflora Differences and the Incidence of Preeclampsia in Pregnant Women in the Early and Middle Stages of Pregnancy - Lei MO, Ping ZHONG (Zhongguo quanke yixue, 2022)
Background Severe preeclampsia can progress to eclampsia and threaten the life safety of mothers and infants, while intestinal flora composition changes may be involved in the occurrence and development of preeclampsia, but there is no clear evidence. Objective To investigate the relationship between intestinal flora differences and the incidence of preeclampsia in pregnant women in the early and middle stages of pregnancy. Methods A total of 455 pregnant women recruited from the Department of Obstetrics, the Second Affiliated Hospital of Guilin Medical University from January 2019 to January 2021 who met the requirements were selected. Pregnant women diagnosed with preeclampsia after 20 weeks of gestation were classified as preeclampsia group (n=32) , and pregnant women without preeclampsia were classified as non-preeclampsia group (n=423) . The clinical data of pregnant women were collected, and fecal samples were collected in the early (≤12+6 weeks) and middle stages of pregnancy (13~27+6 weeks) for bioinformatics analysis of intestinal flora, and the relationship between bioinformatics and the incidence of preeclampsia was analyzed. Results There were statistically significant differences in age, Shannon index and Simpson index in early pregnancy between preeclampsia group and non-preeclampsia group (P<0.05) . Logistic regression analysis showed that age≥35 years old〔OR=1.894, 95%CI (1.432, 2.369) 〕, low Shannon index in early pregnancy〔OR=0.709, 95%CI (0.465, 0.921) 〕 and low Simpson index in early pregnancy〔OR=0.612, 95%CI (0.354, 0.893) 〕 were independent risk factors for preeclampsia (P<0.05) . ROC curve showed that the optimal cut-off value and AUC of Shannon index for predicting the incidence of preeclampsia in pregnant women in early pregnancy were 6.255 and 0.745〔95%CI (0.652, 0.838) 〕, with the corresponding sensitivity and specificity of 76.58% and 60.00%, respectively. The Simpson index in early pregnancy predicted the onset of preeclampsia with the best truncation value of 0.945 and AUC of 0.724〔95%CI (0.623, 0.826) 〕, and the corresponding sensitivity and specificity were 62.90% and 60.61%, respectively. Conclusion Decreased Shannon index and Simpson index of fecal intestinal flora in early pregnancy in early pregnancy are independent risk factors for the occurrence of preeclampsia in pregnant women, and have early predictive value for the onset of preeclampsia.